(untitled) (Global Scientific Review, 2023)
In this article, increasing productivity of labour in network and the issue of decreasing expenses were observed through disseminating modern technologies to the agriculture. Moreover, taking digital technologies’ video through satellite, charting, exact farming, smart farms, smart greenhouses, management of raw-materials, delivering products of agriculture and saving, controlling products of agriculture and transports and lastly, disseminating the Big-data to the agriculture have been illustrated